Platelet Indices in Coronary artery disease with Pre-diabetes” - TALWAR, DHRUV; KUMAR, SUNIL (International Journal of Psychosocial Rehabilitation, 2020)
One of the most common cause of death world over is Coronary artery disease and it comprises a major public health problem in this decade. Increased platelet agglutination in association with other risk factors increase the probability of development of myocardial ischemia .In diabetic patients, the mean platelet volume is increased when comparison was done with subjects who are normal. However, this relationship between Mean platelet volume and pre-diabetes is not evacuated properly. This will be a cross-sectional study, conducted in the Medicine Department, at AVBRH, a tertiary care teaching hospital situated in the rural area of Wardha District. All patients more than 18 years of age, undergoing angiography in cardiology unit of Medicine Department at AVBRH, Sawangi who have given written consent will be added in the study. We expect to establish a relationship between MPV and Coronary artery disease in our subset of population in India and to correlate it with the severity of CAD on angiography. We would also study the relationship between Mean platelet volume and other risk factors of CAD- especially diabetes and pre-diabetes. Will be drawn on completion of study.